Pengaruh Promosi, Harga, Online Customer Rating Dan Gaya Hidup Terhadap Pengambilan Keputusan Pembelian Gofood Pada Aplikasi Gojek Di Kota Malang - Tipliyatul Hasanah; Antin Rakhmawati (LPPM Universitas Buddhi Dharma, 2025)
The rapid development of technology in the era of globalization has brought significant changes in various aspects of life, including in the field of e-commerce and the digital economy. One of the innovations that has emerged is an online food delivery service, with Gojek through the GoFood feature becoming one of the main players in Indonesia. GoFood has become a service that is widely used by the public, excelling in terms of convenience, menu diversity, and transaction security. However, amid its popularity, GoFood faces several challenges. In terms of promotions, there are complaints about confusing terms and invalid promo codes. Prices on GoFood tend to be more expensive than direct purchases due to additional costs. Online rating systems also face problems such as alleged manipulation and lack of objectivity. In addition, the use of GoFood also affects people's lifestyles, potentially encouraging consumptive behavior and reducing direct social interaction. This study aims to measure the influence of promotions, prices, online customer ratings and lifestyle on purchasing decision-making. The population in this study is consumers who use GoFood services with a sample of 272 respondents taken by the non-probability sampling technique (purposive sampling). The analysis method used is multiple linear regression analysis. To obtain the test results in this study, a classical assumption test is carried out. namely normality test, multicollinearity test, heterokedasticity test, autocorrelation test, and then hypothesis test using the Statistical Package for the Social Sciences (SPSS 22). The results of the study show that promotions, prices, online customer ratings, and lifestyle simultaneously have a significant effect on GoFood purchase decisions. Partially, price and lifestyle variables have the most significant influence, followed by price and online customer ratings.